Record book of the estates of William A. Tucker and Margaret Tucker - Tucker, William A., -1849.; Tucker, Margaret, -1854.
Record book containing legal copies of the wills, inventories, and other estate papers of Tucker and his wife, Margaret.
Landowner of Baltimore, Md.
Handwritten transcripts.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Administration of estates -- Maryland -- Baltimore; Wills -- Maryland -- Baltimore; Landowners